Predictor factors of uncontrolled diabetes - Zahra Cheraghi; Amin Doosti-Irani; Parvin Cheraghi; Parham Mohammadi; Marzieh Otogara (BMC Endocrine Disorders)
Abstract Objective The most significant challenge faced by individuals with diabetes is poor blood sugar control. The objective of this review is to identify the most crucial predictors of poor glycemic control among patients with diabetes. Materials This review employed a comprehensive approach, utilizing all available analytical cross-sectional, case control and cohort studies to ascertain the pooled odds ratio/risk ratio of uncontrolled diabetes. The review encompassed articles from international databases, including Web of Science, PubMed, Scopus, and Google Scholar without restrictions on publication date or language. Data extraction was conducted until May 11, 2024, with statistical analyses performed using Stata 17 software, employing a random effects model at a 95% confidence level. Results Out of 157,841 records, a total of 59 cross-sectional studies, 4 case-control studies, and 3 cohort studies were included, comprising 284,558 participants with a mean age of 53.78 years (SD = 6.33). There was no statistically significant association between the seven factors analyzed—age, gender, smoking status, education level, systolic blood pressure, diastolic blood pressure, and BMI. However, we observed a significant decrease in the likelihood of poor glycemic control with each unit increase in physical activity. Specifically, as physical activity levels increased, the likelihood of poor glycemic control decreased (adjusted OR 0.41; 95% CI: 0.24, 0.72; p-value = 0.02). Conclusion Our systematic review and meta-analysis study showed that increased levels of physical activity in individuals with type 2 diabetes enhance the chances of achieving better glycemic control.